Serapan Hara, Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica rapa L.) yang Dibudidayakan Secara Organik dengan Aplikasi Vermikompos - Nisma Ula Shoumi Rahmawati (Folium : Jurnal Ilmu Pertanian, 2021)
The quality of vermicompost is determined by the kinds of media materials used, the degree ofmaturity, the worm species used and the manufacturing process. In this study using plantpakkoy pakkoy (Brassica rapa L.). The purpose of this study was to determine the optimumdose of three kinds of vermicompost for N, P and K nutrient uptake and growth response andyield of mustard pakcoy (Brassica rapa L.). The research was conducted at Agricultural Land inLandungsari Village, Dau District of Malang Regency with height ± 544 m asl. This research is afield experiment using factorial randomized block design (RAK) with control. Factor 1: VariousVermicompost Materials Factor 2: Application Dose. The resulting data were analyzed variance(ANOVA) with 5% BNJ and 5% Dunnet. Regression analysis was performed to find the optimumdose of vermicompost. The results showed that the growth and production of mustard plantpakcoy using vermicompost showed higher yield compared to control. In the treatment of V2D2(coconut husk + cow dung + leaf litter + rice straw + leftover vegetables with dose of 10 ton ha-1).